Parity and the risks of adverse birth outcomes: a retrospective study among Chinese - Li Lin; Ciyong Lu; Weiqing Chen; Chunrong Li; Vivian Yawei Guo (BMC, 2021)
Abstract Background Nulliparity is considered to be a risk factor of preterm birth (PTB), low birth weight (LBW) and small for gestational age (SGA). With the new two-child policy launched in 2016, more Chinese women have delivered their 2nd baby. Yet few studies have assessed the impact of parity on adverse birth outcomes in China. This study aimed to examine the association between parity and risks of PTB, LBW and SGA in a Chinese population. The combined effects of maternal age and parity on adverse birth outcomes were also assessed. Methods This retrospective study included all non-malformed live births born during January 1, 2014 and December 31, 2018 in Chengdu, China. A total of 746,410 eligible live singletons with complete information were included in the analysis. Parity was classified into nulliparity (i.e. has never delivered a newborn before) and multiparity (i.e. has delivered at least one newborn before). Log-binomial regression analyses were applied to evaluate the association between parity and PTB, LBW and SGA. We further divided maternal age into different groups (< 25 years, 25-29 years, 30-34 years and ≥ 35 years) to assess the combined effects of maternal age and parity on adverse birth outcomes. Results Multiparity was associated with reduced risks of PTB (aRR = 0.91, 95% CI: 0.89-0.93), LBW (aRR = 0.74, 95% CI: 0.72-0.77) and SGA (aRR = 0.67, 95% CI: 0.66-0.69) compared with nulliparity. In each age group, we observed that multiparity was associated with lower risks of adverse birth outcomes. Compared to nulliparous women aged between 25 and 29 years, women aged ≥35 years had greater risks of PTB and LBW, regardless of their parity status. In contrast, multiparous women aged ≥35 years (aRR = 0.73, 95% CI: 0.70-0.77) and those aged < 25 years (aRR = 0.88, 95% CI: 0.84-0.93) were at lower risk of SGA compared with nulliparous women aged between 25 and 29 years. Conclusion Multiparity was associated with lower risks of all adverse birth outcomes. Special attention should be paid to nulliparous mothers and those with advanced age during antenatal care, in order to reduce the risks of adverse birth outcomes.